Answer:
x = (5 + 3a)/(2a - b)
General Formulas and Concepts:
<u>Pre-Algebra</u>
Step-by-step explanation:
<u>Step 1: Define equation</u>
a(2x - 3) = bx + 5
<u>Step 2: Solve for </u><em><u>x</u></em>
x=(3a+5)/(2a-b)
We spread the a to the 2x and -3 first,
2ax -3a= bx+5 5ax
By adding 3a, we pass the -3a over
2ax=bx+5+3aa bx+5+3aa
We'll pass the bx over the bx, then
2ax-bx=5+3aa-bx=5
Now we will party like this on the left side,
5+3a) x(2a-b)=5+3a)
Everything we have to do to find x is to separate both sides by (2a-b)
x=(3a+5)/=(3a+5)/ (2a-b)
See picture for reply and solution steps.